The last voyage of the Demeter [videorecording (DVD)] - Schut, Bragi F.; Olkewicz, Zak, 1983-; Hawkins, Corey, 1988-; Franciosi, Aisling, 1993-; Dastmalchian, David; Botet, Javier, 1977-; Cunningham, Liam; Briones, Jon Jon, 1965-; Walley, Chris, 1995-; Kapičić, Stefan, 1978-; Furulund, Martin; Nikolaeff, Nikolai; et al. (Universal, 2023)
Dracula's unholy presence dooms the crew of the merchant ship Demeter as it sails from Carpathia to London.